2022
DOI: 10.1093/hropen/hoac018
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and obstetric outcomes are influenced by developmental stage and cryopreservation of transferred embryos after clomiphene citrate-based minimal stimulation IVF

Abstract: STUDY QUESTION Is the embryo transfer method associated with maternal and perinatal outcomes after minimal stimulation IVF using clomiphene citrate (CC)? SUMMARY ANSWER The incidence of pregnancy complications and adverse perinatal outcomes was influenced by the developmental stage (cleavage versus blastocyst stages) and cryopreservation (fresh versus vitrified) of the transferred embryos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Single vitrified‐warmed cleavage stage embryo transfers were performed as previously described. 7 Briefly, SVCT was performed under vaginal ultrasound guidance using a specially designed soft silicone inner catheter (Kitazato Corporation); a single embryo was placed in a minimal volume in the upper part of the uterine cavity on Day 2 after ovulation in a natural cycle. Dydrogesterone (30 mg/day; Mylan EPD G.K.) was administered orally during the early luteal phase after SVCT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single vitrified‐warmed cleavage stage embryo transfers were performed as previously described. 7 Briefly, SVCT was performed under vaginal ultrasound guidance using a specially designed soft silicone inner catheter (Kitazato Corporation); a single embryo was placed in a minimal volume in the upper part of the uterine cavity on Day 2 after ovulation in a natural cycle. Dydrogesterone (30 mg/day; Mylan EPD G.K.) was administered orally during the early luteal phase after SVCT.…”
Section: Methodsmentioning
confidence: 99%
“… 3 The cryopreservation technique enables embryos to be transferred at the optimal time without the detrimental effects of ovarian stimulation on endometrial function; therefore, improved pregnancy outcomes are expected after FETs compared with those after fresh embryo transfers. 4 , 5 , 6 Furthermore, recent studies reported that maternal and perinatal complications could be reduced by the FETs in the natural cycle 7 but not in the hormone replacement cycle. 8 In addition, since the use of preimplantation genetic testing (PGT) has been broadly increasing, 9 , 10 , 11 , 12 , 13 the demand for FETs is expected to continue to increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…A questionnaire was utilised, requesting information regarding the following: date and mode of delivery, sex, birth weight, and length of the newborn(s); presence of any birth defect or other anomaly; and pregnancy complications [ 33 ]. Preterm delivery was defined as delivery occurring at < 37 weeks [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…SVCT was performed under vaginal ultrasound guidance using a specially designed soft silicone inner catheter (Kitazato Corporation), as previously described [18]. A single embryo was placed in a minimal volume in the upper part of the uterine cavity on day 2 after ovulation in a natural cycle.…”
Section: Embryo Transfermentioning
confidence: 99%